Studies on established Acorus calamus (L.) populations - Feigl, Gábor; Szőllősi, Réka; Mihalik, Erzsébet (Acta Biologica Szegediensis, 2010)
The aim of this study was to investigate the sustainability, stress tolerance and growth parameters of an ex situAcorus calamus population as well as the availability of the rhizome segments (ramets) for propagation. The main stress factors for semi aquatic plants, like A. calamus are the competition from dicot weeds and the severe dry conditions. We compared two experimental plots of different competition levels: low competition (moderate weeding) and high competition: without weeding. We noticed that there were differences between the competition levels only in terms of the life span of the leaves and the length of the shoots (aboveground parts). For the propagation we compared the ramets derived from the apical and lateral parts of the rhizomes as vegetative propagules. Plants derived from both types of rhizome parts showed dynamic development. We detected significantly higher leaf numbers in plants grown from lateral rhizome segments. The newly propagated plant population was kept free from weeds. However, its experimental plot was surrounded by a weedy lane. We found that the leaf number is correlated with the spatial arrangement of the individuals, namely the proximity of weeds decreased the leaf number of the plants in the periphery of the plot.